2022
DOI: 10.1093/tas/txac123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supplemented undenatured type II collagen on pain and mobility in healthy Labrador Retrievers during an exercise regimen

Abstract: The aim of this experiment was to evaluate the effect of undenatured type II collagen supplementation on inflammation and pain using gait analysis and industry-accepted pain and mobility questionnaires during an exercise regimen in healthy dogs. Forty healthy Labrador Retrievers (20 male/20 female; Range: 5-12yrs) were sorted into two groups: undenatured type II collagen group receiving 40mg UC-II product (10mg total collagen and ≥3% undenatured type II collagen) and placebo group receiving 40mg maltodextrin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Of the two studies evaluating the combination of undenatured type II collagen and Boswellia serrata, only one study was a prospective randomised placebo-controlled trial [37], while the other one was a clinical trial and did not have a control group [36]. Of the total articles reviewed, 21 of the studies used undenatured type II collagen and Boswellia serrata for the management of OA, and 5 of them used this feed supplements for helps support joint health after intensive exercise or in patients with diseases that predispose to OA, such as hip and elbow dysplasia or medial patellar luxation [52,[61][62][63]66].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the two studies evaluating the combination of undenatured type II collagen and Boswellia serrata, only one study was a prospective randomised placebo-controlled trial [37], while the other one was a clinical trial and did not have a control group [36]. Of the total articles reviewed, 21 of the studies used undenatured type II collagen and Boswellia serrata for the management of OA, and 5 of them used this feed supplements for helps support joint health after intensive exercise or in patients with diseases that predispose to OA, such as hip and elbow dysplasia or medial patellar luxation [52,[61][62][63]66].…”
Section: Resultsmentioning
confidence: 99%
“…The pain assessment questionnaires completed by the owners and veterinarians showed favourable results after the use UC-II ® [60,[65][66][67]. The results obtained using quantitative methods for the gait analysis showed an improvement in step force [57,58,66]. In healthy dogs subjected to intense exercise, supplementation with UC-II ® led to increased speed of movement and activity per kilometre [63].…”
Section: Undenatured Type II Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…The undenatured form of type II collagen (UC-II) is a nutraceutical derived from the cartilage of chicken sternum (Bagi et al 2017) and has recently been shown to prevent the increase of pro-inflammatory and cartilage degeneration biomarkers in Labrador retrievers (Varney et al 2022). Previous research has shown that UC-II has greater efficacy compared to other supplements such as glucosamine-hydrochloride and chondroitin-sulphate (Gupta et al 2012).…”
Section: Collagenmentioning
confidence: 99%
“…The popularity of collagen supplementation has increased not only for humans but also for animals, particularly dogs. Several recent studies have examined the positive effects of collagen supplementation in dogs, including during the treatment of osteoarthritis (Stabile et al, 2022 ) or joint diseases (Cabezas et al, 2022 ), as well as in healthy dogs during an exercise regimen (Varney et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%